Evidence-informed physical therapy management of performance-related musculoskeletal disorders in musicians - Chan, Cliffton; Ackermann, Bronwen (Frontiers in Psychology, 2014)
Playing a musical instrument at an elite level is a highly complex motor skill. The regular daily training loads resulting from practice, rehearsals and performances place great demands on the neuromusculoskeletal systems of the body. As a consequence, performance-related musculoskeletal disorders (PRMDs) are globally recognized as common phenomena amongst professional orchestral musicians. These disorders create a significant financial burden to individuals and orchestras as well as lead to serious consequences to the musicians’ performance and ultimately their career. Physical therapists are experts in treating musculoskeletal injuries and are ideally placed to apply their skills to manage PRMDs in this hyper functioning population, but there is little available evidence to guide specific injury management approaches. An Australia-wide survey of professional orchestral musicians revealed that the musicians attributed excessively high or sudden increase in playing-load as major contributors to their PRMDs. Therefore, facilitating musicians to better manage these loads should be a cornerstone of physical therapy management. The Sound Practice orchestral musicians work health and safety project used formative and process evaluation approaches to develop evidence-informed and clinically applicable physical therapy interventions, ultimately resulting in favourable outcomes. After these methodologies were employed, the intervention studies were conducted with a national cohort of professional musicians including: health education, onsite injury management, cross-training exercise regimes, performance postural analysis, and music performance biomechanics feedback. The outcomes of all these interventions will be discussed alongside a focussed review on the existing literature of these management strategies. Finally, a framework for best-practice physical therapy management of PRMDs in musicians will be provided.